Gender Assessment for CGIAR Initiative: Sustainable Intensification of Mixed Farming System (SI-MFS) Project - Tsige, Meseret; Najjar, Dina (International Center for Agricultural Research in the Dry Areas, 2024)
Findings presented in the following slides are collected and analyzed from 20 women and 20 men in-depth interview participants as well as from focus group with a total of 40 discussants, from 4 focus group discussions, where least endowed, middle class and youth men and women have been involved was used as a source. Two Development Agents interviews have been also used to generate findings.